2022
DOI: 10.3389/fnut.2022.934568
|View full text |Cite
|
Sign up to set email alerts
|

Association of fruits, vegetables, and fiber intake with COVID-19 severity and symptoms in hospitalized patients: A cross-sectional study

Abstract: Background and aimsFruits and vegetables are rich in fiber and a good source of anti-inflammatory and immune-boosting vitamins, minerals, and antioxidants. We investigated the association between fruits, vegetables, and fiber intake and severity of COVID-19 and related symptoms in hospitalized patients.MethodsA total of 250 COVID-19 hospitalized patients aged 18 to 65 years were recruited for this cross-sectional study in Kashan, Iran, between June and September of 2021. Dietary intakes were assessed using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Considering the well-known beneficial effects of fruits on health, we hypothesized that we would find higher daily consumption of fruits, but, interestingly, with the exception of stone fruits, daily fruit consumption was rather low compared to vegetables and fermented foods. In fact, there are studies that found the negative association of fruits consumption and COVID-19 [48]. In the study that identified foods that contain chemical compounds with bioactive properties that resemble clinically approved drugs for COVID-19, they identified 52 phytochemical compounds with anti-SARS-CoV-2 effects [18].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the well-known beneficial effects of fruits on health, we hypothesized that we would find higher daily consumption of fruits, but, interestingly, with the exception of stone fruits, daily fruit consumption was rather low compared to vegetables and fermented foods. In fact, there are studies that found the negative association of fruits consumption and COVID-19 [48]. In the study that identified foods that contain chemical compounds with bioactive properties that resemble clinically approved drugs for COVID-19, they identified 52 phytochemical compounds with anti-SARS-CoV-2 effects [18].…”
Section: Discussionmentioning
confidence: 99%
“…The target Ca:Mg for both is 2.0. A fiber rich diet that includes fermented vegetables is inversely proportional to Covid-19 mortality in Europe 122,123 , as demonstrated in Germany (sauerkraut) and South Korea ((kimchi) 124 .…”
Section: Vitamin D and Ca:mgmentioning
confidence: 91%
“…Vajargah et al observed positive effects in COVID-19 patients also. Study participants who consumed more fruits, vegetables and fiber were less likely to develop severe COVID-19, required less corticosteroids and antiviral medication, and had lower inflammatory markers (i.e., CRP) and a significantly shorter length of hospital stay and convalescence [ 39 ]. Dysbiosis triggered by binding of SARS-CoV-2 to ACE2 receptors on the surface of enterocytes or by circulating cytokines could cause a leaky gut, which in turn favors the entry of bacterial products and toxins [ 40 ].…”
Section: Diet Recommendations Diet Quality and Covid-19mentioning
confidence: 99%